Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Berpikir Kritis Materi Bahasa Indonesia Siswa Kelas IV - Rivana Maheswara; Muhib Rosidi (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Indonesian children must have comprehensive skills to compete globally, including effective communication, critical thinking, morality, civic responsibility, tolerance, and adaptability at the global level. Teachers can apply a problem-based learning model that involves real investigation, analysis, problem identification, hypothesis, experiment, and inference to build comprehensive skills. The purpose of this study is to determine how fourth grade students at SDN Kemayoran 13 use critical thinking skills influenced by learning with a problem-based model. Through the use of the quasi-experiment design method, the population is about 33 students who are separated into experimental and control groups. Initial observations and descriptive tests were conducted to collect data. Homogeneity, normality, and hypothesis tests were used in data analysis, while data presentation used tables. This study shows the results of using a problem-based paradigm in learning to increase students' capacity to think critically in Indonesian language subjects for grade IV students at SDN Kemayoran 13. This is shown by the t-test analysis that produces data with a 2-tailed significance value of 0.000 < 0.05, which leads to the conclusion that H0 is rejected and Ha is accepted. This finding shows that the teaching paradigm with a problem-based model has an effect on the critical thinking of grade IV students at SDN Kemayoran 13.